The perception towards sissy in the workplace : Case study at KWSP, LIGS and Tourism Board / Azlie Ibrahim - Ibrahim, Azlie (2009)
The purpose of this study was to see the perception and acceptance of working people towards sissy in the workplace. As sissy is part of the human being, it is very important to give equal right and opportunity to sissy as other ordinary person has. Beside that, nowadays the involvement of sissy in the workplace is significant to the organization as well as to the economic scale of the country as a whole. Therefore, the study was conducted at three public organizations which were Kumpulan Wang Simpanan Kerja (KWSP), Lembaga Industri Getah Sabah (LIGS) and Tourism Board. The study focused on what are the perception of working people and their acceptance towards sissy. Hence a set of questionnaire was distributed to 150 respondents of those three organizations. The result showed that the perception of the respondents not significantly influenced by the religion factor, residential area, age and gender of the respondents. Beside that, the researcher also concluded that the perception of the respondents towards sissy at the workplace was generally positive. People at the workplace were found to accept the existence of sissy.